The Significance of States with the Largest Defense Allocations (In Millions of US Dollars at Current Prices and Exchange Rates) to Corruption Issues - Endro Tri Susdarwono; Alma Wiranta (Political Sciences Program Study, 2024)
The defense sector will always be vulnerable to corruption, due to risks from high levels of secrecy, complex technical procurement, and exploitation of the hierarchical nature of the military. This study aims to provide a description of the significance of the country's largest defense allocation (in millions of US at current prices and exchange rates) to corruption. The approach used in this research is descriptive quantitative. The data used uses the country's CPI (Corruption Perception Index) issued by TII and the country's defense allocation issued by SIPRI. Data analysis used the method of testing the hypothesis through the khai-square distribution. This study concludes that the number of countries with CPI below the average of the 50 countries with the largest defense allocation (in millions of US at current prices and exchange rates) is not constant and therefore the cause is a significant factor. meaning that it can be interpreted that countries with large defense allocations tend to have a CPI below the average.